Aldehyded Dextran and ε-Poly(L-lysine) Hydrogel as Nonviral Gene Carrier - Yumiko Togo; Katsu Takahashi; Kazuyuki Saito; Honoka Kiso; Boyen Huang; Hiroko Tsukamoto; Suong-Hyu Hyon; Kazuhisa Bessho (Hindawi Limited, 2013)
Background. The expression term of the gene transfected in cells needs to belong enough inorder to make a gene therapy clinically effective. The controlled release of the transfected gene can be utilized. The new biodegradable hydrogel material created by 20 w/w% aldehyded dextran and 10 w/w% ε-poly(L-lysine) (ald-dex/PLL) was developed. We examined whether it could be as a nonviral carrier of the gene transfer. Methods. A plasmid (Lac-Z) was mixed with ald-dex/PLL. An in vitro study was performed to assess the expression of Lac-Z with X-gal stain after gene transfer into the cultured 293 cells and bone marrow cells. As a control group, PLL was used as a cationic polymer. Results. We confirmed that the transfection efficiency of the ald-dex/PLL had a higher transfection efficiency than PLL in 293 cells (plasmid of 2 μg: ald-dex/PLL 1.1%, PLL 0.23%, plasmid of 16 μg: ald-dex/PLL 1.23%, PLL 0.48%). In bone marrow cells, we confirmed the expression of Lac-Z by changing the quantity of aldehyded dextran. In the groups using ald-dextran of the quantity of 1/4 and 1/12 of PLL, their transfection efficiency was 0.43% and 0.41%, respectively. Conclusions. This study suggested a potential of using ald-dex/PLL as a non-carrier for gene transfer.